Role of Neutrophil / Lymphocyte Ratio in Diabetes 2 Nephropathy (Medical Forum Monthly, 2020)
Objective: To study the role of Neutrophil / lymphocyte ratio in diabetes 2 nephropathyStudy Design: Observational / cross sectional StudyPlace and Duration of Study: This study was conducted at the Rawal Institute of Medical Sciences Rawalpindi and Idris Teaching Hospital Sialkot during Feb 2018 to Feb 2020.Materials and Methods: It is an observational cross-sectional study. Totally 115 diagnosed type 2 diabetes mellitus patients were registered in this study. NLR was calculated by analyzing differential leukocyte count in complete blood picture. Albuminuria was tested by MICRAL-II TEST strips by dipstick method. Demographic data and laboratory Investigations were recorded on designed Performa. Informed written consent was taken from every patient before collecting the sample, history and examination. Permission of Ethical Committee of the Institute was considered for collection of data and get publishing in medical journal.Results: Totally 115 diabetic patients were registered. About 56 patients had DN and 59 had normal urine albumin. Mean NLR for a normal group is 1.94 ± 0.65 and in DN group is 2.83 ± 0.85 which was highly significant (P < 0.001). Estimated glomerular filtration rate (P = 0.047) and serum glutamate pyruvate transaminase (P < 0.001) were also significant.Conclusion: The results of our study show that there was a significant relation between NLR and DN. Therefore, NLR may be considered as a novel surrogate marker of DN in early stages.